ANALISIS MUTU IKAN TEMBANG (Sardinella fimbriata) DI TEMPAT PELELANGAN IKAN (TPI) BULU, UPT PPP BULU, TUBAN, JAWA TIMUR - Fransisca, Fida; Isroni, Wahyu; Sahidu, Adriana Monica (Jurnal Penelitian Perikanan Indonesia, 2023)
Tembang fish (Sardinella fimbriata) is the dominant and economical fish catch at Technical Unit of Bulu Coastal Fisheries Port (CFP) and is delivered to Bulu Fish Auction Site (FAS) or known as TPI Bulu. Tembang fish has perishable food characteristics, so it is necessary to improve the quality of freshly caught fish by maximising handling methods, facilities, and sanitary hygiene. Fishermen in TPI Bulu still rarely apply cold chain to maintain fish quality and some use formalin because it is easily available and cheap. This study aims to determine the quality of tembang fish at TPI Bulu. Testing parameters include organoleptic test, pH test, TPC test, and formalin test. The results of the research on 90 tembang fish samples obtained an average organoleptic value of 7.00 and pH 6.16. The formalin test results were 32 samples (35.6%) positive for formalin and 58 samples (64.4%) negative for formalin. The average TPC test result was 4.7 x 105 CFU/gr. The results of the inspection of Good Fish Handling Methods (GFHM) 30% of the criteria were fulfilled and 70% of the criteria were not fulfilled.